(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Alexander Arkadevich Fainberg (1939–2009) was one of the most remarkable literary figures in Uzbekistan, known for his poetry, screenwriting, and translations. His works bridge the cultural and linguistic gap between Russian and Uzbek literature, offering profound philosophical insights and artistic beauty. This paper critically analyzes Fainberg’s poetic legacy, focusing on the themes, imagery, and stylistic features of his poetry. Through an in-depth discussion of selected poems, the study explores how his works reflect existential questions, national identity, and universal human emotions. Additionally, this paper examines Fainberg’s influence on the literary community, his role as a translator, and the cultural significance of his works in Soviet and post-Soviet contexts.